(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
The purpose of this review article is to highlight the various approaches for measuring polymer degradation. Different tests (mechanical, thermal, rheological) give good evidence about polymer properties. From these tests, the effect of varying degradation factors on the general properties of the polymer can be estimated. Change in weight, thermal tests, dynamic mechanical analysis tests, structural tests, and the rheological test show the changes in the material behaviour before and after the effect of the different environmental factors.